Wastewater surveillance of enteric viruses in eastern Argentina: High rates of detection and first report of NoV GI.5 and GII.20 - Frydman, Camila Ayelén; Miño, Samuel; Iglesias, Néstor Gabriel; Carballeda, Juan Manuel; Simari, Milagros Belén; Pisano, María Belén; Dus Santos, Maria Jose; Mozgovoj, Marina Valeria (Elsevier, 2024)
Individuals infected with enteric viruses excrete them in their feces for an extended period, whether symptomatic or asymptomatic. This characteristic, combined with the capability of these viruses to persist in the environment, forms the core of our research. The objective of our study was to investigate the presence of viruses associated with diarrhea and hepatitis: Hepatitis A virus (HAV), Hepatitis E virus (HEV), Norovirus GI (NoV GI), Norovirus GII (NoV GII), and Rotavirus (RV) by RT-real time PCR, in untreated wastewater samples (n=100) collected in the period July 2020 to August 2021 from two low-income neighborhoods in the district of La Plata, Buenos Aires, Argentina. Globally, the percentage of positive samples was 25 % for HEV, 27 % for RV, 14 % for NoV GII, 1 % for NoV GI, and no detectable samples were found for HAV. HEV, RV, and NoV GII were detected in most of the studied months, with the highest detection rates of RV and NoV GII during the winter season. Regarding RV positive samples, the gene encoding the VP8* protein of three samples was sequenced and phylogenetic analysis revealed that the detected strains belonged to genotypes P[8] and P[3]. Additionally, four NoV strains were also genetically characterized by amplifying a fragment corresponding to the ORF-1/ORF-2 junction region. The identified strains were NoV GI.5, NoV GII.4, NoV GII.17 and NoV GII.20. Our results provide relevant information and serve as scientific evidence of the importance of considering wastewater analysis as a feasible strategy to determine the circulation of enteric viruses in the population, with the further benefit of predicting emerging strains. Moreover, this study represents the first report of the circulation of NoV GII.20 and GI.5 genotypes in our country. // Resumen: Los individuos infectados con virus entéricos los excretan en las heces durante un período prolongado, ya sea sintomático o asintomático. Esta característica, combinada con la capacidad de estos virus de persistir en el medio ambiente, forma el núcleo de nuestra investigación. El objetivo de nuestro estudio fue investigar la presencia de virus asociados con la diarrea y la hepatitis: virus de la hepatitis A (VHA), virus de la hepatitis E (VHE), norovirus GI (NoV GI), norovirus GII (NoV GII) y rotavirus (RV). ) mediante RT-PCR en tiempo real, en muestras de aguas residuales no tratadas (n=100) recolectadas en el período julio de 2020 a agosto de 2021 de dos barrios populares del partido de La Plata, Buenos Aires, Argentina. A nivel mundial, el porcentaje de muestras positivas fue del 25 % para HEV, 27 % para RV, 14 % para NoV GII, 1 % para NoV GI y no se encontraron muestras detectables para HAV. Se detectaron HEV, RV y NoV GII en la mayoría de los meses estudiados, con las tasas de detección más altas de RV y NoV GII durante la temporada de invierno. En cuanto a las muestras positivas para RV, se secuenció el gen que codifica la proteína VP8* de tres muestras y el análisis filogenético reveló que las cepas detectadas pertenecían a los genotipos P[8] y P[3]. Además, también se caracterizaron genéticamente cuatro cepas de NoV amplificando un fragmento correspondiente a la región de unión ORF-1/ORF-2. Las cepas identificadas fueron NoV GI.5, NoV GII.4, NoV GII.17 y NoV GII.20. Nuestros resultados proporcionan información relevante y sirven como evidencia científica de la importancia de considerar el análisis de aguas residuales como una estrategia factible para determinar la circulación de virus entéricos en la población, con el beneficio adicional de predecir cepas emergentes. Además, este estudio representa el primer informe de la circulación de los genotipos NoV GII.20 y GI.5 en nuestro país.